ACTIVITY TEST OF CINNAMON (Cinnamomum burmannii) LEAVES EXTRACT GEL AGAINST HYDROXYPROLINE LEVELS IN WOUND HEALING - Fathnur Sani K; Humaryanto; Yuliawati; Tia Wida Eka Putri (LLDIKTI X Sumbar, Riau, Jambi, Kepri, 2023)
Wound often occur in daily activities. Cinnamon leaves are widely known to have pharmacological activity. The content of secondary metabolites in cinnamon leaves (Cinnamomum burmanii) is a support for development into pharmaceutical products in wound healing. The aims of this study was to determine the effect of gel preparation on hydroxydiproline levels in cases of Incisions. The research method is an experimental laboratory with a post test only control group design. The test animals used were 5 rabbits with 5 treatment groups, namely positive control (Bioplacenton®), negative control (Gel Base), Formula 1 (Gel Extract 2.5%), Formula 2 (Gel Extract 5%), and Formula 3 (Gel Extract 10%). The preparation was given topically on the back of the rabbit. Observations of hydroxyproline levels were carried out after 14 days of treatment. The results showed that there was a significant difference between the treatment groups (p<0.05) where the best formula was formula 2 with hydroxyproline levels of 44.13µg/mL which had an effectiveness close to positive control. Then followed by formula 3 and formula 1.